The Aspergillus flavus Histone Acetyltransferase AflGcnE Regulates Morphogenesis, Aflatoxin Biosynthesis, and Pathogenicity - Lan, Huahui; Sun, Ruilin; Fan, Kun; Yang, Kunlong; Zhang, Feng; Nie, Xin Y.; Wang, Xiunai; Zhuang, Zhenhong; Wang, Shihua (Frontiers in Microbiology, 2016)
Histone acetyltransferases help regulate fungal development and the production of secondary metabolites. In this study, we determined that the histone acetyltransferase AflgcnE influenced morphogenesis and aflatoxin biosynthesis in Aspergillus flavus. We observed that AflGcnE localized to the nucleus and cytoplasm during the conidial production and germination stages, while it was located mainly in the nucleus during the hyphal development stage. Deletion of AflgcnE inhibited the growth of A. flavus and decreased the hydrophobicity of the cell surface. The ΔAflgcnE mutant exhibited a lack of asexual sporulation and was unable to generate sclerotia. Additionally, AflgcnE was required to maintain cell wall integrity and genotoxic stress responses. Importantly, the ΔAflgcnE mutant did not produce aflatoxins, which was consistent with a significant down-regulation of aflatoxin gene expression levels. Furthermore, our data revealed that AflgcnE is a pathogenicity factor required for colonizing maize seeds. In summary, we revealed that A. flavus AflGcnE is crucial for morphological development, aflatoxin biosynthesis, stress responses, and pathogenicity. Our findings help clarify the functional divergence of GcnE orthologs, and may provide a possible target for controlling A. flavus infections of agriculturally important crops.